2015
DOI: 10.1007/s40093-015-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in-vessel co-composting of yard waste and development of kinetic models for co-composting

Abstract: Background Organic solid waste management is a major challenge in high population density areas like apartments, educational institutions, hospitals, etc., as their disposal with other wastes could not only lead to issues like vector menace, odour generation but also would lead to loss of resources that could be reused such as nutrients which will benefit soil. In places like educational institutions, the major portion of waste generated is organic waste, especially food waste and yard waste from the campus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 29 publications
8
23
0
1
Order By: Relevance
“…In VC and CP the Nt increased at 68 DAE (1.76 ± 0.05% and 1.71 ± 0.13%, respectively), while in SC an increase in Nt was observed at 35 DAE (1.70 ± 0.02%). In all three treatments Nt had increased by 183 DAE, which coincides with Sangamithirai et al (2015) who found an increase in Nt at the end of the SC process with OW from garden and tea leaves, as well as with Fornes et al (2012) who recorded increases of Nt in VC and CP.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In VC and CP the Nt increased at 68 DAE (1.76 ± 0.05% and 1.71 ± 0.13%, respectively), while in SC an increase in Nt was observed at 35 DAE (1.70 ± 0.02%). In all three treatments Nt had increased by 183 DAE, which coincides with Sangamithirai et al (2015) who found an increase in Nt at the end of the SC process with OW from garden and tea leaves, as well as with Fornes et al (2012) who recorded increases of Nt in VC and CP.…”
Section: Resultssupporting
confidence: 84%
“…In VC the percentage of OC dropped sharply by 68 DAE and the subsequent decrease was gradual, which coincides with Garg and Gupta (2011) for the transformation of plant residues and cow manure with E. fetida. The gradual degradation of OC in SC coincides with that mentioned by Sangamithirai et al (2015), when studying gardening and paper residues.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…C/N ratio has been used as an indicator of the potential of compost stability. A mature compost should have an C/N ratio B25 (Sangamithirai et al 2015). The C/N ratio of the final composts was also lower than 12 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Riffaldi et al (1986) studied GI of garden cress and reported that compost is certainly not phytotoxic to plants when GI is more than 80%. Similar to garden cress seeds, germination indexes of at least 80% in radish seeds (Mitelut and Popa 2011) and cucumber seeds (Sangamithirai et al 2015) indicated production of compost which is not phytotoxic. Investigated compost samples in this study recorded germination index higher than those achieved by Kumar et al (2010) during co-composting of green waste and food waste at low C/N ratio using an invessel lab-scale reactor.…”
Section: Compost Qualitymentioning
confidence: 95%